Student-Teacher Gender Matching and Academic Achievement - NaYoung Hwang; Brian Fitzpatrick (SAGE Publishing, 2021)
Scholars have examined the effects of same-gender teachers on student achievement, but the findings are mixed. In this study, we use 7 years of administrative data from students in elementary and middle schools (i.e., Grades 3 through 8) in Indiana to test links between gender matching and student achievement. We find that female teachers are better at increasing both male and female students' achievement than their male counterparts in elementary and middle schools. The positive effects of having female math teachers are particularly large for female students' math achievement, but we do not find evidence for a positive gender matching effect in English language arts. In addition, contrary to popular speculation, boys do not exhibit higher academic achievement when they are assigned to male teachers. Our findings suggest that the effects of teacher gender on student learning vary by subject and gender, but the effect sizes are small.